2005
DOI: 10.3748/wjg.v11.i6.842
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloriinfection in hemodialysis patients: Susceptibility to amoxicillin and clarithromycin

Abstract: Resistance to amoxicillin does not appear to be an important problem in H pylori-infected ESRD and non-uremic patients in our region. In contrast, the rates of resistance to clarithromycin are high, particularly in the ESRD population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…The prevalence of H. pylori infection in patients receiving CAPD and hemodialysis has been shown to be less than or equal to that in healthy subjects in various different geographic populations [17,18,19,20]. Our previous cohort study in 1997 in 539 Japanese hemodialysis patients with a mean treatment duration of 8.4 ± 0.3 years showed a prevalence of H. pylori infection of 48.6% (95% CI 44.3-52.9), which was significantly lower than that in dyspepsia patients with normal renal function (78.5%, 95% CI 74.1-82.4, p < 0.001) or healthy individuals undergoing screening (69.4%, 95% CI 60.3-77.5, p < 0.001) [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of H. pylori infection in patients receiving CAPD and hemodialysis has been shown to be less than or equal to that in healthy subjects in various different geographic populations [17,18,19,20]. Our previous cohort study in 1997 in 539 Japanese hemodialysis patients with a mean treatment duration of 8.4 ± 0.3 years showed a prevalence of H. pylori infection of 48.6% (95% CI 44.3-52.9), which was significantly lower than that in dyspepsia patients with normal renal function (78.5%, 95% CI 74.1-82.4, p < 0.001) or healthy individuals undergoing screening (69.4%, 95% CI 60.3-77.5, p < 0.001) [17].…”
Section: Discussionmentioning
confidence: 99%
“…A recent large-scale Japanese epidemiological study showed that the infection rate has declined to 30-50%, especially in younger patients [16]. The prevalence of H. pylori infection in patients receiving dialysis has been investigated, and in most studies, the infection rate in patients with chronic kidney disease receiving continuous ambulatory peritoneal dialysis (CAPD) and hemodialysis is shown to be equal to or lower than that in subjects with normal renal function in various population groups [17,18,19,20]. Thus, at a time when infection rates of H. pylori are decreasing, the infection rate in hemodialysis patients is also expected to decrease.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to amoxicillin does not appear to be a critical problem in H. pyloriinfected ESRD and non-ESRD patients in Turkey. By contrast, rates of resistance to clarithromycin are high, particularly in the ESRD population [45] . Prospective studies on the optimal therapy protocol, including antibiotic combination, dosage, and duration, in ESRD patients are warranted.…”
Section: H Pylori Therapy In Patients With End-stage Renal Diseasementioning
confidence: 95%
“…According to this change, eradication rates with triple regimens of PPI/amoxicillin/clarithromycin in Japan have decreased from an initial 90.6 to 74.8% [26]. In hemodialysis patients, the incidence of clarithromycin resistance is known to be higher than that in healthy H. pylori -positive subjects, due to the frequent use of clarithromycin in daily practice [27]. In our study, the rate of clarithromycin-resistant strains in hemodialysis patients was high, 45.5%.…”
Section: Discussionmentioning
confidence: 99%